2004
DOI: 10.1038/sj.bjc.6601726
|View full text |Cite
|
Sign up to set email alerts
|

Negative human papillomavirus testing in normal smears selects a population at low risk for developing high-grade cervical lesions

Abstract: High-risk human papillomaviruses (HR-HPV) are the necessary cause of cervical carcinomas and there is an increasing interest in using HR-HPV DNA detection in adjunction to cytological examination for primary cervical screening. To determine whether women with a normal smear negative for HR-HPV DNA detection with the Hybrid Capture II assay might represent a low-risk population for developing a high-grade squamous intraepithelial lesion (HSIL), 4401 women have been followed in a period of 12 -72 months (median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
40
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 32 publications
(35 reference statements)
5
40
0
2
Order By: Relevance
“…The overall detection rate by cytology of 0.3% lesions XCIN3 at baseline and 0.5% after 5 years in this study is comparable to the detection rate of lesions XCIN3 in cervical cancer screening in The Netherlands (Bos et al, 2002;Anttila et al, 2004). The high NPV of the combination of a negative hrHPV test and a normal smear is in accordance with Clavel et al (2004), who reported an NPV of 99.9% in a partly hospital-based population, with a much shorter interval (median 2.8 years) for women of 15 -79 years of age. Sherman reported an NPV of 99.2% for hrHPV in cervical lavage specimens during annual screening for women of 16 -94 years of age (Sherman et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…The overall detection rate by cytology of 0.3% lesions XCIN3 at baseline and 0.5% after 5 years in this study is comparable to the detection rate of lesions XCIN3 in cervical cancer screening in The Netherlands (Bos et al, 2002;Anttila et al, 2004). The high NPV of the combination of a negative hrHPV test and a normal smear is in accordance with Clavel et al (2004), who reported an NPV of 99.9% in a partly hospital-based population, with a much shorter interval (median 2.8 years) for women of 15 -79 years of age. Sherman reported an NPV of 99.2% for hrHPV in cervical lavage specimens during annual screening for women of 16 -94 years of age (Sherman et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…In their 5-year cohort study in The Netherlands of 2810 women aged 30 -60 years with normal cytology, Bulkmans et al (2005) show that, in agreement with previous findings from the US (Sherman et al, 2003), France (Clavel et al, 2004) and the UK (Cuzick et al, 2003;Peto et al, 2004), HR HPV testing combined with cytology has higher sensitivity and higher negative predictive value for cervical intraepithelial neoplasia (CIN) 3 and cancer than cytology alone. Specificity was, however, slightly lower for HPV testing and cytology (93%) than cytology alone (95%).…”
supporting
confidence: 64%
“…Five cases (4 HSIL and 1 micro-invasive carcinoma) were found in 4,401 women (0.1%) after 34 months by Clavel et al 16 Sherman et al 14 reported that during the first 45 months the cumulative incidence of CIN3 was 0.16% in HPV and cytology double negatives. It is not surprising that no CIN2þ was detected by colposcopy/biopsy in random samples of about 200 to 250 women.…”
Section: Discussionmentioning
confidence: 99%